Characterization of Rock Varnish Ferromanganese Crusts on Ancient Egyptian Wall Paintings from Bahariya Oasis, Egypt - Ahmed Elshabrawy; Mona Ali (Shedet, 2021)
The black crust phenomenon appears clearly in the Bannentiu tomb, an ancient Egyptian tomb back to the 26th dynasty in the Bahariya oasis, one of the main iron ores in Egypt’s western desert. The black crusts are attributed to the high content of Fe and Mn oxides and oxyhydroxides components in the sandstone host rock formation as cement materials. Nondestructive investigations were carried out for the collected samples using optical microscopy, XRD, XRF, and SEM–EDX analyses. The observed results indicate that silica, iron, manganese compounds, clay minerals, and other remaining elements classify the black crusts as one of the rock varnish species. The present study aims to analyze and classify the chemical composition and mineralogy of the black crusts formed on the wall paintings of the Bannentiu tomb. Moreover, the study proposes a model formation for the rock varnish on the Bannentiu tomb wall painting. The proposed simulation relies on high ratios of Fe and Mn in the host rock and the microclimatic factors that cause the migration of these elements to the surface, with the oxidization factors giving rise to oxides and hydroxides low crystallinity.